Analysis of performance standards in the educational institution College of Business and Economics, Sulaimaniyah University as a model - Hussein, Ali Jalal; Abd-Ali, Khalid Haidar (Journal of University of Human Development, 2016)
The analysis of performance quality standards in the educational institution considering that it’s one of the most important service sectors which is one of the most important fields in which creativity and scientific research are stimulated in a direction for achieving continuous development as a service for the community. The college of administration and economics in the University of Sulaimaniyah was chosen as example to apply these standards in the frame of instructions that was set by the ministry of higher education in the Kurdistan region as a basis to achieve the reform, change and development in this field.